The Cost of Tolerating Intolerance: Right-Wing Protest and Hate Crimes - Sulin Sardoschau; Annalí Casanueva-Artís (Institute of Labor Economics (IZA), 2025)
Freedom of speech is central to democracy, but protests that amplify extremist views expose a critical trade-off between civil liberties and public safety. This paper investigates how right-wing demonstrations affect the incidence of hate crimes, focusing on Germany's largest far-right movement since World War II. Leveraging a difference-in-differences framework with instrumental variable and event-study approaches, we find that a 20 percent increase in local protest attendance nearly doubles hate crime occurrences. We explore three potential mechanisms—signaling, agitation, and coordination—by examining protest dynamics, spatial diffusion, media influence, counter-mobilization, and crime characteristics. Our analysis reveals that large protests primarily act as signals of broad xenophobic support, legitimizing extremist violence. This signaling effect propagates through right-wing social media networks and is intensified by local newspaper coverage and Twitter discussions. Consequently, large protests shift local equilibria, resulting in sustained higher levels of violence primarily perpetrated by repeat offenders. Notably, these protests trigger resistance predominantly online, rather than physical counter-protests.
Keywords: D74; J15; D83; Z10; D72; 330; refugees; hate crime; signal; protest; right-wing